Relationship of MP ASI Processing with Infant 6 to 12 Months Old Baby Growth and Development (Study at Umi Rahma Maternity Clinic in 2019) - Tetty Rina Aritonang; Wa Ode Ida Fitriani; Riyen Sari Manulang; Farida Mentalina Simanjuntak (Institute of Computer Science (IOCS), 2021)
Complimentary food (MP ASI) is another complimentary food supplied to children from 6-24 months of age, and that accompanies breastfeeding. The research aimed to establish the relationship between different food and growth and infants 6 to 12 months old. This research was conducted at the Umi Rahma maternity clinic from June-July 2019 with a sample of 44 people. The population determines the research sample, and the selection studied is following the research capability in terms of funding and sampling quota time. Analytical survey methods with SPSS analysis that involves Univariate and Bivariate analysis were used in the study. The results showed that the MPASI processing variable had a weak, positive and insignificant effect on infant growth and had a strong, positive, and significant impact on infant development.